EFFECT OF STUDENT PERCEPTION OF ATTENTION PARENTS, PARENTS OF EDUCATION AND LEARNING ACHIEVEMENT OF INTEREST LEARNING ECONOMY CLASS XI IPS SMA PGRI 1 PADANG - Pradana, Eko - (Pendidikan Ekonomi, 2014)
This study aims to analyze: 1) The effect of students perceptions of parental attention on student achievement XI IPS on economic subjects in high school Padang PGRI 1, 2) The effect of parental education on student achievement XI IPS on economic subjects The SMA PGRI 1 Padang, 3) The effect of student interest on student achievement XI IPS on economic subjects at SMA PGRI 1 Padang, 4) the effect of students perceptions of parental supervision, parental education level and interest in learning on student achievement XI IPS on economic subjects at SMA PGRI 1 Padang. This type of research used in this research is descriptive and associative form of causal relationships. The study population was all students in class XI IPS SMA 1 Padang PGRI numbered 128 people. Sampling technique with Simple random sampling with a sample size of 97 people. Data analysis techniques: descriptive analysis and inductive analysis, multiple regression with SPSS version 16.0. The results showed that: 1) There is a positive and significant effect between students perception of parental attention to the learning achievement of economic class XI IPS SMA PGRI 1 Padang. Where the values obtained thitung 9.550> 1.661 ttable of significant value 0.000 <= 0.05. 2) There is a positive and significant impact of parental education on the learning achievement of economic class XI IPS PGRI SMA 1 Padang. Where was obtained for 2,595 tcount> ttable of 1.661 with significant value of 0.011 <= 0.05. 3) There is a positive and significant effect between interest in learning the learning achievement of economic class XI IPS PGRI SMA 1 Padang. Obtained tcount for 2,754> ttable of 1.661 with significant value of 0.007 <= 0.05. 4) There is a positive and significant impact jointly between students perceptions of parental supervision, parental education level and interest in learning the learning achievement of economic class XI IPS PGRI SMA 1 Padang. Where Fhitung obtained at 104.086> Ftable significant value of 2.70 and 0.000 <= 0.05.